Determinants of health literacy in early childhood care among marginalized ethnic communities: a cross-sectional study in three border provinces of Thailand - Nathamon Wutthipan; Kunnara Maneekunwong; Pimkanabhorn Trakooltorwong; Srisuluk Kietmaneerat; Chuntana Reangsing; Khanittha Pitchalard; Salisa Kodyee; Katemanee Moonpanane (International Journal for Equity in Health, 2026)
Abstract Background Early childhood development metrics remain substandard among marginalized ethnic minority communities in three border provinces of Thailand. This study evaluated the levels and determinants of health literacy (HL) among primary caregivers to contextualize its role in mitigating adverse child health outcomes. Methods A community-based, cross-sectional correlational study employing multi-stage cluster random sampling was conducted between July and October 2024. Sample size was determined using an a priori power analysis for multiple linear regression (f² = 0.05, α = 0.05, power = 0.80, 19 predictors), yielding a minimum of 351 participants; 380 caregivers were enrolled. Data were collected using the validated 61-item Parental Health Literacy Scale assessing five HL domains. Multiple linear regression with simultaneous variable entry identified independent determinants of overall HL. Results Among the 380 participants, the largest ethnic group was Thai-Yai (23.95%), followed by Thai-Lue (19.74%), Hmong (19.21%), AKha (17.37%), Lahu (14.47%), Chinese–Yunnan (3.95%), Lee-Soo (1.05%), and Yao (0.26%). Caregivers demonstrated moderate health literacy in the functional, cognitive, critical, and behavioral domains, but exhibited low proficiency in the interactive domain (communicating care needs), resulting in a moderate overall composite score (135.04/199 = 67.9%). Multiple linear regression demonstrated that interpersonal professional support, specifically nurse-led counselling, strongly predicted health literacy proficiency (B = 9.318, p = 0.027). Other significant predictors included receiving information from provincial hospitals (B = 9.013, p = 0.030) and early childhood development centers (B = 7.531, p = 0.032), perceived financial adequacy (B = 3.470, p = 0.013), formal educational attainment (B = 3.064, p = 0.007), and parity (B = 3.252, p = 0.006), identifying primigravida caregivers as a vulnerable demographic. Conclusions Nurse-led counselling, institutional health support from provincial hospitals and early childhood development centers, formal educational attainment, and parity are the primary modifiable determinants of HL in this population. Public health interventions must prioritize face-to-face, culturally congruent caregiver education delivered through dual-tiered institutional networks, with targeted support for first-time mothers.